Asymmetric post-translational modifications regulate the intracellular distribution of unstimulated STAT3 dimers - Cardoso, Beatriz Joana Marques, 1994- (2019)
Tese de mestrado, Neurociências, Universidade de Lisboa, Faculdade de Medicina, 2019